White piedra, black piedra, tinea versicolor, and tinea nigra: contribution to the diagnosis of superficial mycosis - John Verrinder Veasey; Ricardo Bertozzi de Avila; Barbara Arruda Fraletti Miguel; Laura Hitomi Muramatu (Sociedade Brasileira de Dermatologia, 2017)
Abstract Superficial mycoses are fungal infections restricted to the stratum corneum and to the hair shafts, with no penetration in the epidermis; they are: white piedra, black piedra, tinea versicolor, and tinea nigra. This study presents images of mycological tests performed in the laboratory, as well as exams performed at the authors office, in order to improve the dermatologist's knowledge about the diagnosis of these dermatoses, which are common in many countries.